The Influence Of Continental And Analytic Philosophy On the New Thinking of Iran - barkhordari, aref (Advances in Social Sciences Research Journal, 2019)
The aim of this study is a comparative study of the influence of continental and analytical philosophy on the New Thinking of Iran with emphasis on Abdolkarim Soroush and Reza Davari. In Iran society Since the 1960s, the discussions were formed, that these discussions from 1980 onward was more visible in the form of two rival discourse with a focus on Reza Davari and Soroush. Soroush influenced by Popper's philosophy of science, Logical and epistemological accuracies of analytic philosophy, Liberalism and religious interests, he consciously sought to catch up with modernity. But Reza Davari influenced by Heidegger and continental philosophy and with religious and identity interests, defended philosophy and opposed with Logicism, scientism and used western anti-enlightenment pre-assumptions and also religious entrenchment against modern human reason, and discussed anti-modern interpretations. These discourses had an impact on the formation of political, social and religious flows in Iran and each of these flows tended to answer the problems of Iranian society. These two discussions started with the disputes from the beginning of the revolution and reached their peak, but they became closer to each other in recent years.